Cultural representation and ideology : Paul bowles as a romantic americain orientalist - Elkouche, Mohamed (Université Mohamed 1er, Faculté des Lettres et des Sciences Humaines, Oujda, 2005)
This research aims at achieving two main complementary objectives. The first objective consists in studying the question of ideology and its problematic interrelation with the domain of literary creation and cultural representation in general. The second aim consists in exploring and analysing many of Paul Bowels’ literary texts so as to probe and reveal the extent of his affiliation and adherence to the Western Orientalist ideology. Accordingly, this disseration is divided into two basic sections : one dealing theoretically with the problematics of ideology and cultural/literary representation, the other with the practical analysis of Bowles’ discursive products. In the theoretical section, a number of controversial issues – pertaining prinipally to the close and subtle interconnectio between art and ideoloy are raised and explore at lenght. These issues are discussed with reference to the different views and theories of such prominent critics and theoreticians as L. Althusser, M. Bakhtin, R. Barthes, P. Macherey, M. Foucault, E. Said and H. Bhabha. The critical synthesis of all these views and theoretical perspectives has ultimately enable us to form a relaively clear and profound idea not only about the notion of ideology and its close affinity with the concept of ‘discourse’ but also about the inevitable presence of ideology in all cultural/literary discourses like that of Orientalism. In the ‘pratical section’, the focus is shifted to the deconstructive analysis and interpretation of Bowles’ varoious literary texts, including his autobiography, three novels, and many of his short stories, travel accounts and ‘journalistic’ discourses. Besides leading us ti the central conclusion that this author stands in fact as a typical American Orientalist, the different analyses of both his fictional and non-fictional representations have helped to shed much light on how ideology operates within artistic/literary forms, and how it is systematically mediated through the skilful and strategic manipulation of the chief narrative compenents like plot, setting, characters and point of view.
Keywords: English literature; Cultural representation; Ideology; Paul Bowles; Romantic americain orientalist